Increasing Vocabularies through Modified Jigsaw and Recitation for Junior High School - Hudzaifah, Ayu (JET ADI BUANA, 2016)
Teaching English for Junior High School needs more innovative and creative way to take the students more concentration and serious when they learn inside and outside the class with nice manner. Vocabularies such as: carnival, dive, caterpillar, camp, and others may appear difficult to understand for the students when the teacher is using all the words without give and explain the meaning. The easiest and common way is the teacher command the students to open the dictionary and search the meaning. Most of Junior High School Students are critical, active, and moody students based on their ages. If the teacher only give the usual way, they will lazy and bore to follow the class and there is not interesting manner to increase their vocabularies in English. Therefore, it becomes the important task for the teacher to find an effective method to increase the vocabularies that the students find it enjoyable and easy to get the meaning. Jigsaw is one of cooperative teaching method that the students into several groups to teach the other groups in turn. The writer arranges modified jigsaw through Ã¢â‚¬Å“card paperÃ¢â‚¬Â that already divide from easy, middle, and difficult and the students have to pay attention how to run this enjoy method and if they already learn and answer, they move to other group based on the paper card which already answer. After the teacher runs modified jigsaw, the teacher continue with recitation. Recitation means the teacher have to give the student task to learn at home, library, or park to make the students always remember the vocabularies, and when they come back to the class, the students will try to remain and repeat again the vocabularies that already learn outside the class. Thus, the change of students in other groups with modified jigsaw and recitation will make all the students more understand and enriched with many vocabularies to make them easier than before